2019
DOI: 10.3390/cli7100117
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Combined CO2 and O3 Exposures on Net CO2 Assimilation and Biomass Allocation in Seedlings of the Late-Successional Fagus Crenata

Abstract: We examined the effects of elevated CO2 and elevated O3 concentrations on net CO2 assimilation and growth of Fagus crenata in a screen-aided free-air concentration-enrichment (FACE) system. Seedlings were exposed to ambient air (control), elevated CO2 (550 µmol mol−1 CO2, +CO2), elevated O3 (double the control, +O3), and the combination of elevated CO2 and O3 (+CO2+O3) for two growing seasons. The responses in light-saturated net CO2 assimilation rates per leaf area (Agrowth-CO2) at each ambient CO2 concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 70 publications
2
7
0
Order By: Relevance
“…These results suggest physiological alterations at leaf level but no adverse effects of EOZ at individual plant level in the first growing season. Instead, that EOZ increased the total harvested aboveground biomass may indicate overcompensation responses of plant growth, similar to observations made in different species of trees exposed to elevated O 3 (Kitao et al 2015;Tobita et al 2019). Although photosynthetic pigments were not directly measured in the first growing season, the large enrichment of Mg in top leaves by EOZ may relate to enhanced chlorophylls potential, and, thus, increased photosynthates that can lead to more biomass.…”
Section: Ozone Effects On Plant Growth and Biomass Production In Early Spring Of The Second Growing Season (2015)supporting
confidence: 75%
See 1 more Smart Citation
“…These results suggest physiological alterations at leaf level but no adverse effects of EOZ at individual plant level in the first growing season. Instead, that EOZ increased the total harvested aboveground biomass may indicate overcompensation responses of plant growth, similar to observations made in different species of trees exposed to elevated O 3 (Kitao et al 2015;Tobita et al 2019). Although photosynthetic pigments were not directly measured in the first growing season, the large enrichment of Mg in top leaves by EOZ may relate to enhanced chlorophylls potential, and, thus, increased photosynthates that can lead to more biomass.…”
Section: Ozone Effects On Plant Growth and Biomass Production In Early Spring Of The Second Growing Season (2015)supporting
confidence: 75%
“…Despite the negative effects of EOZ on leaf-level physiology, EOZ-treated plants displayed a small increase in plant height, old shoot dry mass, and total aboveground dry mass, which may indicate overcompensation responses similar to the biomass production of the first growing season and observations in different studies with other species exposed to elevated O 3 (Kitao et al 2015;Tobita et al 2019). Contrariwise, EDU400 increased new shoot dry mass and total aboveground dry mass, compared EDU0-treated plants, irrespective of O 3 treatment, a finding suggesting that shrubs in both AOZ and EOZ were under stress.…”
Section: Edu Impact Against O 3 Effects On Plant Physiology Growth and Biomass Production In The Second Growing Season (2015)mentioning
confidence: 81%
“…Effect of Elevated CO 2 and/or O 3 Concentrations on Q. mongolica Growth Elevated CO 2 concentrations enhanced stem growth, resulting in increased leaf, stem, and aboveground biomass (Table 1). This suggests that the growth of Q. mongolica seedlings was accelerated by an elevated CO 2 concentration, as reported for many other tree species (e.g., Richet et al, 2012;Tobita et al, 2019). Conversely, we observed minor changes in biomass growth under the elevated O 3 concentration condition (Table 1), unlike in other species (e.g., Watanabe et al, 2007;Richet et al, 2012), whose growth and biomass have been shown to decrease under such conditions.…”
Section: Discussionsupporting
confidence: 83%
“…We used the same experimental design and facility as those of Tobita et al (2019), although the experimental period (1 growing season) was shorter than that of Tobita et al (2019), who used much smaller seedlings (1-year-old) than those in the present study (2-year-old). Q. mongolica seedlings were grown in FACE systems.…”
Section: Experimental Designmentioning
confidence: 99%
“…Compared with Japanese white birch, E. makinoi had about half S/R ratio, which suggests a greater amount of carbohydrate allocation into the root system. Japanese white birch preferably allocates biomass into shoot (Kitao et al, 2015(Kitao et al, , 2021bTobita et al, 2019), which might contribute to height growth, while compensating lower total biomass compared to E. makinoi across the water treatments.…”
Section: Photosynthesis and Growth Responses In Pot-grown Seedlings O...mentioning
confidence: 99%